Economic Digitalization for Community Empowerment: A Literature Review - Isnaini, Fadlila; Mulyono, Dewangga Aqna Musthofa; Mas’ud, Fuad (Research Horizon, 2024)
In recent decades, the creative economy has become a dynamic and rapidly growing sector globally, as well as in Indonesia. The evolution of consumer behavior in the digital age presents an opportunity for small and medium enterprises (MSMEs) to increase market reach, but also entails a challenge in adapting to these changes. Market segmentation becomes more extensive due to the presence of an online marketplace for the sale of goods and services. Online marketplace companies require a competitive advantage to distinguish themselves from similar businesses. The aim of this scoping review was to assess the role of technology in the creative economy in terms of fostering community empowerment and promoting sustainable development. The studies reviewed were chosen from electronic databases specifically Google Scholar and Emerald covering the years 2020 to 2024. The study's findings indicate that technology is essential for bolstering and advancing the creative economy sector, with a particular emphasis on community empowerment and sustainable development. The advancement of technology has facilitated wider entry into global markets, spurred innovation in products and services, and reinforced the conservation and promotion of local cultural heritage. Case studies from different regions in Indonesia illustrate how technology can empower local communities and facilitate inclusive and eco-friendly economic growth.